The relationship between physical activity and overactive bladder among American adults: a cross-sectional study from NHANES 2007–2018 - Tianen Wu; Binbin Xu (Scientific Reports)
Abstract This study aimed to explore the association between physical activity (PA) and the risk of Overactive Bladder (OAB) in American adults. This analysis comprises a cross-sectional study of comprehensive population data collected from the National Health and Nutrition Examination Surveys spanning the years 2007 to 2018. Adults were categorized into four PA patterns (inactive, insufficiently active, weekend warrior, and regularly active) based on self-reported PA levels. We employed a weighted logistic regression model, restricted cubic spline (RCS) analysis, and subgroup analyses to investigate the relationship between PA patterns and OAB. This research included 17,050 subjects. After thorough adjustments for covariates, multivariate logistic regression models revealed that weekend warrior, and regularly active adults had a reduced risk of OAB compared with inactive adults, with odds ratios (ORs) of 0.96 (95% CI 0.94, 0.98), and 0.97 (95% CI 0.95, 0.99), respectively. RCS analysis revealed a nonlinear relationship between total weekly PA duration (in minutes) and the incidence of OAB, with approximately 915.41 min of total PA duration (minutes per week) associated with the lowest risk of OAB. This study demonstrated that adults engaging in either the regularly active or weekend warrior patterns experienced a lower risk of OAB compared to inactive adults. PA could be considered as part of a broader strategy for OAB prevention.